Impact of a 2-Day Critical Care Ultrasound Course during Fellowship Training: A Pilot Study. (5th August 2015) - Dinh, Vi Am; Giri, Paresh C.; Rathinavel, Inimai; Nguyen, Emilie; Hecht, David; Dorotta, Ihab; Nguyen, H. Bryant; Chrissian, Ara A.
Abstract : Objectives . Despite the increasing utilization of point-of-care critical care ultrasonography (CCUS), standards establishing competency for its use are lacking. The purpose of this study was to evaluate the effectiveness of a 2-day CCUS course implementation on ultrasound-naïve critical care medicine (CCM) fellows. Methods . Prospective evaluation of the impact of a two-day CCUS course on eight CCM fellows' attitudes, proficiency, and use of CCUS. Ultrasound competency on multiple organ systems was assessed including abdominal, pulmonary, vascular, and cardiac systems. Subjects served as self-controls and were assessed just prior to, within 1 week after, and 3 months after the course. Results . There was a significant improvement in CCM fellows' written test scores, image acquisition ability, and pathologic image interpretation 1 week after the course and it was retained 3 months after the course. Fellows also had self-reported increased confidence and usage of CCUS applications after the course. Conclusions . Implementation of a 2-day critical care ultrasound course covering general CCUS and basic critical care echocardiography using a combination of didactics, live models, and ultrasound simulators is effective in improving critical care fellows' proficiency and confidence with ultrasound use in both the short- and long-term settings.